2008
DOI: 10.3168/jds.2007-0821
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling of Soybean Curd Residue and Wet Brewers Grains With or Without Other Feeds as a Total Mixed Ration

Abstract: Wet brewers grains and soybean curd residue were stored in laboratory-scale silos without (BG and SC silages, respectively) or with other ingredients as total mixed rations (BGT and SCT silages, respectively). Silages were opened after 14 and 56 d, and microbial counts, fermentation products, and aerobic stability were determined. Denaturing gradient gel electrophoresis was carried out to examine bacterial communities, and several bacteria that appeared to be involved in fermentation were identified. Lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 22 publications
6
61
2
4
Order By: Relevance
“…They are frequently isolated from plant material, e.g. fresh vegetables, cassava and silage (Wang and Nishinno 2008), cacao beans (De Bruyne et al 2008), as well as from meat and meat products (Milbourne 1983;Collins et al 1993;Han et al 2010;Patterson et al 2010;Han et al 2011;Comi and Iacumin 2012;Doulgeraki et al 2012;Kesmen et al 2012), fish (Tanasupawat et al 2000;Liu et al 2009), kimchi (Choi et al 2002;Jang et al 2002;Lee et al 2002), specialties from Malaysia (Björkroth et al 2002), soil (Magnusson et al 2002) and, in isolated cases, they can also occur in clinical material of human or animal origin. In such cases, they are of course associated with other bacteria.…”
Section: Characteristic and Occurrence Of Weissella Sppmentioning
confidence: 99%
“…They are frequently isolated from plant material, e.g. fresh vegetables, cassava and silage (Wang and Nishinno 2008), cacao beans (De Bruyne et al 2008), as well as from meat and meat products (Milbourne 1983;Collins et al 1993;Han et al 2010;Patterson et al 2010;Han et al 2011;Comi and Iacumin 2012;Doulgeraki et al 2012;Kesmen et al 2012), fish (Tanasupawat et al 2000;Liu et al 2009), kimchi (Choi et al 2002;Jang et al 2002;Lee et al 2002), specialties from Malaysia (Björkroth et al 2002), soil (Magnusson et al 2002) and, in isolated cases, they can also occur in clinical material of human or animal origin. In such cases, they are of course associated with other bacteria.…”
Section: Characteristic and Occurrence Of Weissella Sppmentioning
confidence: 99%
“…Members of the genus Weissella have been isolated from a variety of sources, such as fresh vegetables, fermented silage (Dellaglio and Torriani, 1986;Ennahar et al, 2003;Wang and Nishinno, 2008), meat or meat products (Milbourne, 1983;Santos et al, 2005;Koort et al, 2006), desert spring and desert plants (Holzapfel and van Wyk, 1982), sugar cane, carrot juice, row milk and sewage (Hammes and Vogel, 1995), milking machine slime (Kandler et al, 1983), soil (Magnusson et al, 2002), fermented sausages (Collins et al, 1993), Korean kimchi (Choi et al, 2002;Lee et al, 2002;Kim and Chun, 2005), Malaysian foods (Leisner et al, 1999;Bjö rkroth et al, 2002) or fermented mescal of Agave salmiana (Escalante- Minakata et al, 2008). But only Weissella confusa and Weissella cibaria have been described from human or animal clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ensiled TMR (referred to as eTMR or TMR silage) has been expanded because of its long-term preservation and favourable nutritional changes due to lactic acid fermentation. Studies on eTMR have increased in recent years, particularly in Asian counties that are usually in humid climate (Nishino et al, 2004;Wang and Nishino, 2008;Weinberg et al, 2011). Recently, it was reported that eTMR using whole-crop rice and rice bran leads to low methane production in vitro and in vivo, compared to TMR which was not ensiled (Cao et al, 2010a;Cao et al, 2012), resulting in the decrease of feed energy loss.…”
mentioning
confidence: 99%